2017
DOI: 10.1038/nprot.2017.127
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell microscopy of suspension cultures using a microfluidics-assisted cell screening platform

Abstract: Studies that rely on fluorescent imaging of non-adherent cells that are cultured in suspension, such as Escherichia coli, are often hampered by trade-offs that have to be made between data-throughput and imaging resolution.. We developed a platform for microfluidics-assisted cell screening (‘MACS’)that overcomes this trade-off by enabling high-throughput and automated single-cell microscopy for a wide range of types and sizes of cells. Since cells can be rapidly sampled directly from a suspension culture, MACS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…After that, we grew the cells in three different conditions: under no pressure, under low pressure (69 kPa) and under higher pressure (103 kPa). These values were chosen based on the typical values used on the MACS (Microfluidic Activated Cells Screening) device, which is a microfluidic device used for pressing cells mechanically [ 25 , 26 ]. After 4 h (when most cells in the population have already had at least one daughter), we measured again the distribution of gene expression in the population and observed statistically significant changes which confirm that pressure can affect gene expression ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, we grew the cells in three different conditions: under no pressure, under low pressure (69 kPa) and under higher pressure (103 kPa). These values were chosen based on the typical values used on the MACS (Microfluidic Activated Cells Screening) device, which is a microfluidic device used for pressing cells mechanically [ 25 , 26 ]. After 4 h (when most cells in the population have already had at least one daughter), we measured again the distribution of gene expression in the population and observed statistically significant changes which confirm that pressure can affect gene expression ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…Such microfluidic devices work better for RLS measurements than micromanipulators but have two major drawbacks: First, the trapping method subjects cells to mechanical pressure, which could bias the results, as we do not know how pressure affects the aging process in unicellular organisms. It has been demonstrated that mechanical pressure affects physiological processes such as growth rate [ 23 , 24 ] and diffusion rates of intracellular components [ 25 , 26 ]. Second, all the published devices require microfabrication techniques with resolution under 5 µm.…”
Section: Introductionmentioning
confidence: 99%
“…This is challenging for several reasons: First , it is straightforward to sample cultures at different times, manually 13 or with microfluidic automation 14 , but such snap-shots provide little information about the progression of events or the connection between heterogeneity and growth 15 . The dynamics of fluctuations are also important e.g.…”
Section: Mainmentioning
confidence: 99%
“…Either way, because the heterogeneity is so substantial and so profoundly changes the fate of stressed cells, effective studies of bacterial responses to stress and starvation should ideally monitor individual cells as they enter and exit stationary phase. This is challenging for several reasons: First, though it is straightforward to sample cultures at different times, either manually 13 or with microfluidic automation 14 , this only provides snapshots of the heterogeneity. The dynamics of fluctuations are also important, since rapidly changing heterogeneity is easily time-averaged by affected processes while slowly changing heterogeneity can effectively establish cell states.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging single‐cell technologies have made significant progress toward revealing the heterogeneity of the single cell. With the capability of miniaturizing fluid control to size scales, microfluidics has been emerging as a leading technology for the single cell capture, preservation, and analysis . Currently, extensive microfluidics‐based techniques have been developed for the single‐cell high‐throughput analysis, including droplet‐based microfluidics, valve‐based microfluidics, and compartment‐based microfluidics.…”
Section: Cells‐on‐chipsmentioning
confidence: 99%